Marketing Constraints to Goats in the Western Hill of Nepal (Nepal Agriculture Research Journal, 2014)
Goat marketing study was conducted in eleven districts with the objectives of exploration  the existing goat marketing system in western hills of Nepal. The methodology of the study  was households survey, Rapid Marketing Appraisal and use of secondary data. Some of the  marketing centers are at the village level, catchments, terminal level markets and district  headquarters. There are some marketing agents dealing with the goat marketing from village  to the municipalities. Goat marketing agents mainly found farmers and middlemen at the  village level and catchments markets. In terminal markets mainly wholesalers and  middlemen were involved where as in district headquarters and municipalities middlemen,  wholesalers and butchers were dealing the goat business. 59.3% respondents believed that  middlemen visit in the village for goat marketing. Almost all farmers sell their goats on the  basis of estimated price. Major constraints on goat marketing were lack of public goat  marketing centres, lack of communications about goat marketing and lack of infrastructure  etc in all the domestic markets. In the western hills of Nepal main goat marketing centre was  found in Pokhara sub municipality where traders/whole sellers bring their goats to sale from  different catchments. Government has the provision of establishing new goat marketing  centers in each VDCs and district headquarters.Nepal Agric. Res. J. Vol. 8, 2007, pp. 95-102DOI: http://dx.doi.org/10.3126/narj.v8i0.11601